New realities in postpandemic: emerging dynamics in teaching, production and dissemination of scientific knowledge (Ágora de Heterodoxias, 2021)
There have been many dynamics that have arisen as a result of the COVID-19 pandemic in the world,this situation has generated new educational stakes and dynamics to which researchers have had to adapt forthe production and dissemination of knowledge and to be able to respond to current social problems. In thiscontext, humanity has been transformed in terms of access to information and socialization mechanisms,with this teaching has also been evolving and presenting technologically with alternatives, but at the sametime, various emotional conditions that have left the confinement to which people have been subjected havealso arisen. Without failing to highlight the hope that has been maintained despite the emotional woundsand dizzying changes in the dynamics of life, which demand the management of major changes fromteaching, access to information, production and socialization of knowledge and thus be able to mitigate theconsequences of the pandemic, which has affected all social orders and human beings in general.
Keywords: New realities in postpandemic; Teaching alternatives; Production and socialization of knowledge